2021
DOI: 10.1111/ene.14692
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain levels reflect outcome in a patient with glutamic acid decarboxylase 65 antibody–positive autoimmune encephalitis under immune checkpoint inhibitor therapy

Abstract: Neurological immune‐mediated side effects are rare but often severe complications of immune checkpoint inhibitor (ICI) treatment. This report describes a severe case of nivolumab/ipilimumab‐associated glutamic acid decarboxylase 65–positive autoimmune encephalitis. It proposes neurofilament light chain levels, a biomarker indicating axonal damage, in the cerebrospinal fluid and serum as a putative novel biomarker for this diagnostically and therapeutically challenging entity with an often unfavorable outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Six patients suspended ICI immediately after the onset of AE symptoms. Piepgras et al reported a patient whose treatment with nivolumab was continued after controlling symptoms with steroids and infliximab but died after the encephalitis symptoms recurred [ 36 ]. In contrast to the previously reported patient, our patient had a good prognosis at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Six patients suspended ICI immediately after the onset of AE symptoms. Piepgras et al reported a patient whose treatment with nivolumab was continued after controlling symptoms with steroids and infliximab but died after the encephalitis symptoms recurred [ 36 ]. In contrast to the previously reported patient, our patient had a good prognosis at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, in contrast with previous reports [3,23], a high percentage of patients tested positive for autoantibodies, mostly to intracellular antigens. The inclusion of patients with novel reactivities such as NIF, TRIM46 [14,[19][20][21] or uncharacterized antibodies may explain this discrepancy and highlights the importance of using tissue-based assays to detect antibodies that could be missed by commercially available kits, both in patients presenting with an iRAE and in patients who will start ICI treatment [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 61 full-text articles were assessed and 27 of them fulfilled inclusion criteria. Five more records were included from other sources, and thus 32 articles reporting 46 patients were included in the qualitative synthesis ( [10][11][12][13][14][15][16][17][18][19][20][21][22] and Data S1). The detailed PRISMA flow chart of the systematic review is reported in Figure 1, whilst relevant data of the included patients are summarized in Table 1.…”
Section: Re Sultsmentioning
confidence: 99%
“…Emerging therapies such as antibody immunotherapy and CAR-T cells may also induce neurotoxicity, particularly autoimmune encephalitis, and the Immune Cell Associated Neurotoxicity Syndrome (ICANS), 1 week after treatment. In the case of post-immunotherapy autoimmune encephalitis, blood and CSF NfL rises and this result might be useful for tolerance monitoring (Piepgras et al, 2021 ). A very recent study reports that patients with ICANS after CAR-T therapy had elevated NfL levels (Schoeberl et al, 2022 ) and increased levels correlated with severity of the symptoms [(ICANS grade 0–1: 28.4 pg/ml (IQR, 19.2–49.7 pg/ml); ICANS grade 2–4: 60.0 pg/ml (IQR, 31.7–109.0 pg/ml); p < 0.01; Schoeberl et al, 2022 )].…”
Section: Nfl and Neurological Damagesmentioning
confidence: 99%